Tests of agility, reaction speed and velocity for tennis Testes de agilidade, velocidade de reação e velocidade para o tênis de campo - Monte A. (2007)
The general objective of this paper is to publicize the development of a battery of tests of reaction speed, agility and velocity for tennis, called TATAM. The current composition includes tests of reaction speed, agility (approach to the net and service) and velocity (forwards, backwards and sideways running). The battery simulates game situations in which tennis players have to take decisions during the test and react using tennis techniques. What sets TATAM apart are the automatic timings in milliseconds and the implementation of situations in which players have to demonstrate their capacity in terms of reaction speed, which is as present in a game of tennis as are the basics. The system allows for the detection of moments when athletes have problems performing movements similar to those of a real game, making it possible to perfect their technique. The tests measure that which they propose to measure in an environment and with movements similar to those of a game of tennis. The system captures data in a consistent and reproducible manner. The report allows for analyses to be performed both individually and by category, both numerically and by classification. This test battery is of great value to coaches and athletes seeking excellence in sport since it allows for movements that are causing problems for sporting performance to be understood.